Kesejahteraan Subjektif Mahasiswa di Tinjau dari Dukungan Sosial dan Stres Akademik - Aditya, Muhammad Rizky; Suhesty, Aulia (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
The college environment is often characterized by the dominance of the role of students who must undergo various academic burdens. Continuous demands in lectures and the presence of piling assignments have a negative impact on subjective well-being in students. Therefore, this study aims to analyze the extent to which perceptions of support in the social environment and academic pressure can affect subjective well-being in students. This study was conducted using a quantitative approach. A total of 101 students of the Faculty of Law, Mulawarman University were used as research subjects who had been selected through a simple random sampling technique. The instruments used in data collection consisted of a subjective well-being scale, a social support perception scale, and an academic stress scale. The analysis was carried out by applying the multiple linear regression method. Based on the test results, it was indicated that the variables of social support and academic stress together had a significant effect on subjective well-being, with an F value of 37.194, an R² value of 0.432, and a p value of 0.000. This means that the influence of social support and academic stress on subjective well-being in students can be accepted statistically.